Efektivitas Pengelolaan Alokasi Dana Desa di Desa Mekar Jaya Kecamatan Sebulu Kabupaten Kutai Kartanegara Tahun 2021 - Wiwin Puji Ningsih; Burhanudin; Anwar Alaydrus (Jurnal Ilmu Pemerintahan, 2022)
This study aims to determine and analyze the level of effectiveness in managing Village Fund Allocations in Mekar Jaya Village, Sebulu District, Kutai Kartanegara Regency in 2021 and to identify the inhibiting factors. This type of research uses qualitative research and data collection, namely through interviews, observation and documentation, while the technique of determining informants uses a layered random sampling technique with a disproportionate stratified random sampling approach as informants, namely the people of Mekar Jaya village based on their level of education, This study focuses on measuring the level of effectiveness in the field of development and empowerment based on James I Gibson's theory consisting of (1) Clarity of purpose; (2) strategy clarity; (3) The process of analysis and formulation of policies; (4) careful planning; (5) preparation of programs that are right on target; (6) Availability of facilities and infrastructure; (7) control and supervision system. The results of the study show that the management of Village Fund Allocations is in the ineffective category. This can be seen from the discrepancy between the use of Village Fund Allocations and the Regulations and the benefits of implementing Village Fund Allocations have not been felt by the community. The ineffectiveness of the Village Fund Allocation is due to factors that affect both internal factors such as incompetent human resources, lack of closeness to the community, lack of community support and external factors such as uncertainty in the process of disbursing funds, the Covid-19 pandemic and changing policies which are then analyzed through SWOT.